Control systems engineering - Nise, Norman S. 4 0 16; 5 (Singapore : John Wiley & Sons (Asia), 2011)
An overview of control system engineering that covers modeling in the frequency and time domains; time response; reduction of multiple subsystems; stability; steady-state errors; root locus and frequency response techniques; design via root locus, frequency response, and state space; and digital control systems.
1. Introduction 2. Modeling in the frequency domain 3. Modeling in the time domain 4. Time response 5. Reduction of multiple subsystems 6. Stability 7. Steady-state errors 8. Root locus techniques 9. Design via root locus 10. Frequency response techniques 11. Design via frequency response 12. Design via state space 13. Digital control systems App. A. List of symbols App. B. MATLAB tutorial App. C. MATLAB's Simulink tutorial App. D. LabVIEW tutorial.
Includes bibliographical references and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Automatic control.;Systems engineering.;Cybernetics.;Electric controllers.;Servomechanisms.;Systems engineering; 20; 2